OPERASI UDARA KHUSUS TNI ANGKATAN UDARA MENGHADAPI ANCAMAN SESAR LEMBANG - Tri Nur Addin; Adi Subiyanto; Muhamad Ikhsan (GoAcademica Research dan Publishing, 2022)
The theory in this research is the theory of special air operations, disaster theory, vulnerability, regional capacity, risk, and resilience. The research method uses qualitative methods with source triangulation techniques using GIS and Powersim software. The results of this study are, first, the implementation of OPDPB through Preliminary Operations (Territorial Task Force, Information Task Force, Air Base Elements, Pasgat Task Force, and Aviation Support Task Force), Basic Operations (Information Task Force, Joint Task Force, C-130 Transport Element, Helicopter Element), Termination Operations (Legal Task Force, Info Task Force). Second, the geospatial map of the distribution of multi-hazard risk levels with a Low-Risk level of 0.32 (Kabupaten Purwakarta and Subang), and a High-Risk level of 0.68% (Bandung Regency, West Bandung Regency, Cimahi City, Bandung City, and Sumedang Regency). Third, recommendations for disaster risk reduction by reducing the value of social vulnerability, physical vulnerability, economic vulnerability, and environmental vulnerability through strengthening resilience (PSBB, local wisdom, volunteers) to face the threat of the Lembang Fault.